(untitled) - Phillips, Deborah (New York, 2002)
Over 1,000 questions that cover each section of the test . Skills practice exercises for each of the language skills presented in the text . Introductory-level practice tests that simulate the format and timing of the actual paper TOEFL test . Pop-up explanations for all practice and test items. Record-keeping to monitor student progress
Keywords: English language; Study and teaching